ESG Impact on Market Performance of Firms: International Evidence - Sahut, Jean-Michel; Pasquini-Descomps, Hélène (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2015)
This study investigates how news-based scores in ESG (Environmental, Social, and corporate Governance) may have influenced the monthly stocks’ market return in Switzerland, the US, and the UK during the 2007–2011 period. We find that the variation of the overall ESG score is only significant in the UK. We also show that the changes in sub-category ratings of GRI (namely, governance, economic, environment, labor, human rights, society, and products) exhibit a small but significant impact on the stock’s performance during limited periods or on limited sectors, which varies among the countries. Finally, our non-parametric kernel regression highlights that the function linking a stock’s performance to its ESG-score changes is probably non-linear.